Persekongkolan Tender dalam Pengadaan Barang Jasa Secara Elektronik pada Pengadaan Pekerjaan Jasa Konstruksi : Analisis Kasus Putusan Perkara Nomor 24/KPPU-I/2020 - Wibowo, Sigit (Universitas Proklamasi 45, 2022)
The purpose of this study is to examine and analyze the occurrence of tender conspiracy in the implementation of electronic procurement of goods/services (e-procurement) in government project construction work contracts. This study uses normative legal research methods, namely by analyzing the principles, rules/norms of applicable laws and regulations and describing existing phenomena and analyzing them systematically.The normative legal research method studied is library material or secondary data, which includes primary and secondary legal materials. With a statute approach and a case approach related to the regulation and application of laws and regulations regarding the procurement of goods and services electronically (e-procurement) and the effect of tender conspiracy in construction service contracts on government project activities according to Indonesian positive law.The suggestion from the researcher is the need to issue higher regulations for the procurement of government goods and services in the form of a law, which has broad binding power in the aspect of procurement and strengthening law enforcement related to the procurement of goods and services by the government. These efforts are intended to suppress the abuse of authority/interests from the auction committee, business actors and auction participants so as to create healthy business competition, namely that there is no bid rigging in government project activities.